STUDI PENGGUNAAN ANTIBIOTIK PASIEN PNEUMONIA ANAK DENGAN METODE DDD DAN DU 90% - Farah Bidara; Mumfasiroh Saputri; Dyah Aryani Perwitasari; Intan Fatah Kumara; Muhammad Ardhani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Pneumonia is one of the most common respiratory infections. The treatment of pneumonia mostly uses broad-spectrum empirical antibiotics that are susceptible to resistance. One of the efforts to reduce antibiotic resistance is to use antibiotics wisely which can be done by regularly evaluating the quantitative and qualitative use of antibiotics. The purpose of this study was to determine the quantity of consumption and the type of antibiotic used in patients pneumonia child inpatient ward at Hospital Mitra Paramedika Yogyakarta (MPY) and Yadika Pondok Bambu Jakarta (YPBJ) by DDD (Defined Daily Dose) and DU (Drug utility) 90%. This is a descriptive study period June 2017 - April 2020 in pediatric patients aged 1 - 18 years with a diagnosis of pneumonia. Sampling was performed at the Medical Record Installation. The Data taken were antibiotic type, dosage regimen, medication route, antibiotic duration (day), and hospital stay (day) as well as patient demographic data (age, type sex) .There are differences in the pattern of antibiotic use between YPBJ and MPY. Comparison of DDD and DU 90% may be due to differences in standard of therapy used by physicians, antibiotic resistance, differences in germ maps and hospital formularies. Keywords: Pneumonia, Children, Antibiotic, Defined Daily Dose, DU 90%